2012
DOI: 10.1080/10255842.2012.671307
|View full text |Cite
|
Sign up to set email alerts
|

The effect of calcification on the structural mechanics of the costal cartilage

Abstract: The costal cartilage often undergoes progressive calcification with age. This study sought to investigate the effects of calcification on the structural mechanics of whole costal cartilage segments. Models were developed for five costal cartilage specimens, including representations of the cartilage, the perichondrium, calcification, and segments of the rib and sternum. The material properties of the cartilage were determined through indentation testing; the properties of the perichondrium were determined thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 53 publications
2
37
0
Order By: Relevance
“…1,6-8 Although the etiology of prostatic calcification remains unclear, calcification of the urethra can result in urethral stiffness, similar to other tissues. 9,10 We evaluated the association among prostatic calcification, urinary symptoms, and urinary flow rate, especially focusing on periurethral calcification (PUC).…”
Section: Resultsmentioning
confidence: 99%
“…1,6-8 Although the etiology of prostatic calcification remains unclear, calcification of the urethra can result in urethral stiffness, similar to other tissues. 9,10 We evaluated the association among prostatic calcification, urinary symptoms, and urinary flow rate, especially focusing on periurethral calcification (PUC).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it was recently reported that increasing the relative volume of calcification in CCG from 0% to 24% increased the stiffness of the costal cartilage segments by a factor of 2.3-3.8. [12] These results suggest that calcification may have a substantial effect on the stiffness of the costal cartilage especially when used in high-stress region such as dorsal nasal augmentation.…”
Section: Discussionmentioning
confidence: 96%
“…PC has no determined cause, however anatomical differences between healthy and PC individuals have been reported in literature. It is believed that the genesis of PE is due to growth complications of the costal cartilages, the medium of attachment for the ribs to the sternum (Cobben et al, 2014;Forman & Kent, 2014) (Figure 1-3). In response, theories of PC developing due to cartilage overgrowth have been suggested.…”
Section: Etiology Of Pectus Carinatummentioning
confidence: 99%
“…The ribs and sternum are bridged via costal cartilages. Being the primary connections of the ribcage, costal cartilages influence the distribution of applied forces to the chest wall (Forman & Kent, 2014). These forces can originate from internal tasks such as breathing, or external sources such as CPR compressions.…”
Section: Costal Cartilagesmentioning
confidence: 99%
See 1 more Smart Citation